2011
DOI: 10.1093/nar/gkr344
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific error profile of Illumina sequencers

Abstract: We identified the sequence-specific starting positions of consecutive miscalls in the mapping of reads obtained from the Illumina Genome Analyser (GA). Detailed analysis of the miscall pattern indicated that the underlying mechanism involves sequence-specific interference of the base elongation process during sequencing. The two major sequence patterns that trigger this sequence-specific error (SSE) are: (i) inverted repeats and (ii) GGC sequences. We speculate that these sequences favor dephasing by inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
454
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(479 citation statements)
references
References 39 publications
14
454
0
3
Order By: Relevance
“…Only sequences identified to at least genus level were kept for further analyses and grouped according to their taxonomic assignment. Finally, we checked our sequences for the typical error base sequence GGC in Illumina amplicon sequencing (Nakamura et al 2011), but this sequence did not occur as an error in our sequences. As the morphology-based approach always led to at least a genus level identification, the two approaches are thus comparable on the analysed taxonomic level.…”
Section: Genetic Diatom Approachmentioning
confidence: 99%
“…Only sequences identified to at least genus level were kept for further analyses and grouped according to their taxonomic assignment. Finally, we checked our sequences for the typical error base sequence GGC in Illumina amplicon sequencing (Nakamura et al 2011), but this sequence did not occur as an error in our sequences. As the morphology-based approach always led to at least a genus level identification, the two approaches are thus comparable on the analysed taxonomic level.…”
Section: Genetic Diatom Approachmentioning
confidence: 99%
“…To eliminate or greatly reduce errors it is also possible to apply sophisticated algorithms that filter out errors. This can only be done with errors that exhibit some consistent patterns related to the library preparation and sequencing steps[116] and not feasible for errors that appear at random. Interestingly, a recent approach to the identification of rare variants utilized the PCR amplification step in the (Illumina) library preparation to identify families of templates carrying the same mutation, which then could be inferred to have been present in the original template molecule as a real mutation[115]…”
Section: Mps Applications In Mutation Analysismentioning
confidence: 99%
“…It is known that base-call errors are more likely towards the ends of reads and that surrounding sequence motifs influence error frequencies [2,10,15]. For example, errors are more likely at positions preceded by GG or following a number of GGC motifs [10], but regardless of the preceding motif, errors become more likely towards the end of reads [2]. However, we have found that errors at some genomic positions appear with greater frequency than can be explained by these effects, and we refer to this as systematic error.…”
Section: Introductionmentioning
confidence: 99%